For the People, By the Viewpoints? Realism and Idealism in Public Reason - Jayaram, Athmeya (Journal of moral philosophy, 2020)
Abstract Since John Rawls, public reason theorists have attempted to show how liberal political norms could be acceptable to people with diverse religious and ethical viewpoints. However, these theories overlook the importance of the distinction between acceptability to realistic people and acceptability to viewpoints, which matters because public reason theories are committed to the former, but only deliver the latter, thereby failing to justify liberal norms. Public reason theories therefore face a dilemma: abandon realistic people and lose normative appeal, or retain realism and find a new way to justify liberalism.